Producción y análisis bromatológico del hongo ostra (Pleurotus ostreatus), cultivado con sustratos de cáscara de cacao, plátano, coco y raquis de palma africana - Lindao Pérez, Jocelyn Daniela (2016)
This research was carried out in the area of Rumiologia, laboratory located in the finca experience "La Maria" of the State Technical University of Quevedo, which aimed to determine the production and bromatologic analysis of the oyster mushroom (Pleurotus ostreatus), cultivated in different substrates, using the design completely random, with six replications per treatment, substrates used in Radial growth were , T1 (PDA), T2 (PDA + cocoa shell), T3 (PDA + rachis of Palm), T4 (PDA + banana peel), T5 (PDA + coconut shell), being the best treatment with 66.83 measures the T5 mm 168 hours, while in production of mushrooms of p. ostreatus T1 (cocoa shell), T2 (rachis of Palm), T3 (banana peel), T4 (coconut shell), which obtained the highest production was T1 with 164.13 g/kg of substrate , not having production in T2 (PDA + RP) was ruled out for the next variable chemical composition, this treatment with higher protein levels was the T4 (PDA + BCC) while than analyses of M.S, E.E, F.B, ELNN, AC, T1 comes with the highest percentages 9405, 6.52, 12.34, 56.15, 3.32 respectively. In the present investigation in all the variables in the study were no significant differences (p ≤ 0.05) to the Tukey test. Concluding that with most composite lignocellulosic substrates are best for obtaining seed and production of the fungus Pleurotus ostreatus with highest percentage of protein, to be considered as a protein food, while that in substrates that retain moisture have an excellent production. For this reason it is recommended that working with fibrous waste keep them constantly wet for their little absorbent ability they will quickly lose moisture